2019
DOI: 10.1182/blood-2019-122510
|View full text |Cite
|
Sign up to set email alerts
|

Oral Arginine Therapy As a Novel Adjuvant in the Management of Acute Pain in Children with Sickle Cell Anemia in Nigeria: A Randomized Placebo-Controlled Trial

Abstract: Introduction: Severe vaso-occlusive pain episodes (VOE) are a major cause of morbidityand mortality in sickle cell anemia (SCA). Low arginine bioavailability is associated with pain severity and predicts need for pediatric hospitalization (Morris et al, 2000). Arginine supplementation has opioid-sparing effects and was found to significantly decrease pain scores in children hospitalized with SCA-VOE compared to placebo in a phase-2 randomized placebo-controlled trial (RCT) performed in the United States (US, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A very small number of clinical studies involving nutritional interventions in SCD patients in African countries were identified. There were four randomized trials [ 88 91 ]. The first was a study of 125 SCD patients in Nigeria (involving children aged 1 year and above) that tested the effect of lime juice on SCD parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A very small number of clinical studies involving nutritional interventions in SCD patients in African countries were identified. There were four randomized trials [ 88 91 ]. The first was a study of 125 SCD patients in Nigeria (involving children aged 1 year and above) that tested the effect of lime juice on SCD parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The final randomized study identified involved the regular administration of oral arginine therapy to 35 hospitalized patients with SCD in Nigeria and compared the effects with 33 control subjects. Plasma arginine levels increased by 125% in the arginine arm compared with 29% in the control arm [ 91 ]. Arginine treatment was associated with quicker discharge and reduced pain events.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma arginine levels increased by 125% in the arginine arm compared with 29% in the control arm. [80] Arginine treatment was assocated with quicker discharge and reduced pain events. The rate of adverse events was non-signi cant between the two treatment arms, however there was a trend towards increased vomiting in the patients treated with arginine.…”
Section: Resultsmentioning
confidence: 99%
“…A very small number of clinical studies involving nutritional interventions in SCD patients in African countries were identified. There were four randomized trials [88][89][90][91]. The first was a study of 125 SCD patients in Nigeria (involving children aged 1 year and above) that tested the effect of lime juice on SCD parameters.…”
Section: Interventional Studiesmentioning
confidence: 99%